Draw a unit circle, centered on the origin. Label the origin "A".
Draw a radius R connecting the origin to point "B" on the circle, such that the angle between the positive x-axis and the new radius equals t.
Draw a vertical line connecting point B with the x-axis. Label the point where the line intersects the x-axis "C".
You now have a right triangle ABC.
By definition of sine, the length BC equals sin t
By definition of cosine, the length AC equals cos t
Since the circle is a unit circle, and AB is a radius of that circle, the length of AB equals 1.
According to the Pythagorean theorem, it follows that sin^2t+cos^2t=1.
2007-01-04 20:16:06
·
answer #1
·
answered by Bramblyspam 7
·
1⤊
0⤋
Using trig identities.
sin^2(t) = (1 - cos(2t))/2
cos^2(t) = (1 + cos(2t))/2
sin^2(t) + cos^2(t) = (1 - cos(2t))/2 + (1 + cos(2t))/2
= (1 - cos(2t) + 1 + cos(2t))/2
= 2/2
= 1
2007-01-05 05:37:26
·
answer #2
·
answered by Kookiemon 6
·
1⤊
0⤋
in a right triangle, let r be the hypotenuse:
cos(t) = x / r â x = rcos(t)
sin(t) =y / r â y= rsin(t)
by pythagorean theorem:
x² + y² = r²
substitute the above definitions:
r²cos²(t) + r²sin²(t) = r²
divide by r²
cos²(t) + sin²(t) = 1
QED
2007-01-05 06:07:49
·
answer #3
·
answered by cp_exit_105 4
·
1⤊
0⤋
sin^2t+cos^2t=1
sin^2t+cos^2t=1
1=1
2007-01-05 08:28:31
·
answer #4
·
answered by Anonymous
·
0⤊
0⤋
We know that sin=perpendicular/hypotenuse and cos=base/hypotenuse.
Therefore if in a right-angled triangle one acute angle is t,we may say that its sin^2+cos^2=(Perpendicular/hypotenuse)^2 +(base+hypotenuse)^2
=Perpendicular^2/hypotenuse^2 +base^2/hypotenuse^2
=(Perpendicular^2+base^2)/hypotenuse^2
=hypotenuse^2/hypotenuse^=1 proved
2007-01-05 05:49:24
·
answer #5
·
answered by alpha 7
·
1⤊
0⤋
sine=opposite/hypotenuse or o/h
cosine=adjacent/hypotenuse or a/h
(a/h)^2+(o/h)^2=(1/h)^2(o^2+a^2) from the pythagorean theorem a^2+p^2=h^2 so (1/h)^2(o^2+a^2)=(1/h)^2(h^2)=1
2007-01-05 04:20:11
·
answer #6
·
answered by yupchagee 7
·
1⤊
0⤋
sin(t) = opposite/hypotenuse
cos(t) = adjacent/hypotenuse
also, the Pythagorean theorem says that
(adjacent)^2 + (opposite)^2 = (hypotenuse)^2
so...
sin^2t + cos^2t = (opp/hyp)^2 + (adj/hyp)^2
= (opp)^2/(hyp)^2 + (adj)^2/(hyp)^2
=[(opp)^2 + (adj)^2]/(hyp)^2
and, using Pythagorus, we have
[(opp)^2 + (adj)^2]/(hyp)^2 = (hyp)^2/(hyp)^2 = 1
2007-01-05 04:43:28
·
answer #7
·
answered by Biznachos 4
·
1⤊
0⤋